The Influence Of Compliance With Prolanis Participants On Blood Sugar Levels In Type 2 DM Patients In 3 Health Centers In Cirebon City - Bambang Wibisono; Mavisiurohmah, Mavisiurohmah; Atik Sutisna (Sean Institute, 2023)
Type 2 DM was a chronic disease that caused major morbidity and mortality, like other chronic diseases. Various management efforts undertaken by patients with type 2 DM none other but aimed at controlling the blood glucose levels in patients. The government launched a program from the Health Social Security Organizing Agency (BPJS) named the Chronic Disease Management Program (PROLANIS). Purpose : This study aims to determine the effect of PROLANIS compliance participants on blood sugar levels in patients with type 2 DM. Method : This research was an observational study with a cross-sectional design using the Simple Random Sampling technique. The number of samples obtained is 50 samples. Primary data were obtained from a questionnaire filled out by PROLANIS participants with type 2 diabetes. Result : The results of the analysis used the spearmen correlation test that there was no effect between education compliance to increase knowledge (p = 0.316), PROLANIS exercises (p = 0.633), and taking medication (p = 0.633) on blood sugar levels of type 2 DM patients. The relationship (p = 0.038) between adherence to carry out medical nutritional therapy to the levels of GDS of type 2 DM patients. Conclusions : There was no effect between education compliance to increase knowledge, PROLANIS exercises, and taking medication of PROLANIS participants on blood sugar levels of patients with type 2 diabetes. The effect between adherence to carry out medical nutritional therapy to the levels of GDS of type 2 DM patients.